Emotional marketing: a review of the use of emotions in advertising and product promotion - Sanchez, Maria Valeria Gasca (Revista JRG de Estudos Acadêmicos, 2025)
Emotional marketing is a strategy that leverages consumers' emotions to create an affective connection with brands, influencing their purchasing decisions. This article presents a review of the use of emotions in advertising and product promotion, highlighting the effectiveness of emotional strategies in building strong brands and fostering customer loyalty. The study discusses how emotions are employed to engage the target audience, particularly in the digital context. It also analyzes how brand identity and the personalization of advertising messages contribute to the success of campaigns. Furthermore, it explores the ethical implications of emotional marketing, emphasizing the importance of balancing emotional appeal with corporate social responsibility.